Challenges in mental health care in the Family Health Strategy - Consuelo Helena Aires de Freitas; Maria Salete Bessa Jorge; Ana Zaiz Teixeira de Carvalho; Diego Muniz Pinto; Cinthia Mendonça Cavalcante (Universidade de Fortaleza, 2011)
Objective: To discuss the practice of mental health care performed by healthcare professionals from the Family Health Strategy in Fortaleza-CE, Brazil. Methods: This is a critical and reflective study conducted in six Basic Health Units in Fortaleza-Ce. The study subjects were 12 health workers of the following professions: doctor, nurse, community health agents and technical and/or nursing assistant. Semi-structured interviews, systematic observationand questionnaire were used for data collection. The empirical analysis was based on an understanding of the discourses through critical hermeneutics. Results: It was evident that the mental health services are developed by some health workers in the ESF, such as, matrix support, relational technologies, home visits and community group therapy. However, there is still deficiency in training/coaching by most professionals in primary care, due to anenduring model of pathological or curative health care. Conclusion: Mental health care is still occasionally held by some workers in primary care. However, some progresses are already present as matrix support, relational technologies in health care, home visits andcommunity therapy.